Proteins journey—from marine to freshwater ecosystem: blood plasma proteomic profiles of pink salmon Oncorhynchus gorbuscha Walbaum, 1792 during spawning migration - Kochneva, Albina; Efremov, Denis; Murzina, Svetlana A. (Frontiers in Physiology, 2023)
The pink salmon (Oncorhynchus gorbuscha) is a commercial anadromous fish species of the family Salmonidae. This species has a 2-year life cycle that distinguishes it from other salmonids. It includes the spawning migration from marine to freshwater environments, accompanied by significant physiological and biochemical adaptive changes in the body. This study reveals and describes variability in the blood plasma proteomes of female and male pink salmon collected from three biotopes—marine, estuarine and riverine—that the fish pass through in spawning migration. Identification and comparative analysis of blood plasma protein profiles were performed using proteomics and bioinformatic approaches. The blood proteomes of female and male spawners collected from different biotopes were qualitatively and quantitatively distinguished. Females differed primarily in proteins associated with reproductive system development (certain vitellogenin and choriogenin), lipid transport (fatty acid binding protein) and energy production (fructose 1,6-bisphosphatase), and males in proteins involved in blood coagulation (fibrinogen), immune response (lectins) and reproductive processes (vitellogenin). Differentially expressed sex-specific proteins were implicated in proteolysis (aminopeptidases), platelet activation (β- and γ-chain fibrinogen), cell growth and differentiation (a protein containing the TGF_BETA_2 domain) and lipid transport processes (vitellogenin and apolipoprotein). The results are of both fundamental and practical importance, adding to existing knowledge of the biochemical adaptations to spawning of pink salmon, a representative of economically important migratory fish species.